2022
DOI: 10.1111/cea.14257
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of cough without a cold in early childhood and associations with atopic diseases

Abstract: Background: Although children can frequently experience a cough that affects their quality of life, few epidemiological studies have explored cough without a cold during childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Divaret-Chauveau et al and Rancière et al investigated cough without cold and dry night cough trajectories, respectively. [28, 38] Both studies used only cough questions collected at different time points to define cough trajectories/patterns, but they included children who wheeze; and the children were also younger (Table S6). In an analysis stratified by presence or absence of wheeze, Divaret-Chauveau et al found physician-diagnosed asthma reported among a small proportion of children in all cough trajectories (2 to 12%) even in the absence of wheeze.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Divaret-Chauveau et al and Rancière et al investigated cough without cold and dry night cough trajectories, respectively. [28, 38] Both studies used only cough questions collected at different time points to define cough trajectories/patterns, but they included children who wheeze; and the children were also younger (Table S6). In an analysis stratified by presence or absence of wheeze, Divaret-Chauveau et al found physician-diagnosed asthma reported among a small proportion of children in all cough trajectories (2 to 12%) even in the absence of wheeze.…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis stratified by presence or absence of wheeze, Divaret-Chauveau et al found physician-diagnosed asthma reported among a small proportion of children in all cough trajectories (2 to 12%) even in the absence of wheeze. [28] Rancière et al also reported physician-diagnosed asthma ever in all cough patterns (7 to 26%) but this included children who wheeze. [38] In our study, parent-reported, physician-diagnosed asthma ever was also reported in all identified cough phenotypes, yet in much higher proportions (22 to 55%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations